Some Ecological Aspects of the Infection of the Mugilid fish Liza abu with the Acanthocephalan Neoechinorhychus iraqensis in Al-Najaf province, Iraq - Taher, J. H.; Abid, N. H.; Al-Hadithi, N. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A total of 803 specimens of the mugilid fish Liza abu was collected from different fishing grounds in Al-Najaf province during the period from Octber 1990 till September 1991. Of these fishes, 9.3% were infected with the acanthocephalan Neoechinorhynchus iraqensis with an intensity of 1.8.Changes in percentage incidence coincided with those of mean intensity. Generally, percentage incidence and intensity increased with the increase of fish length (age). Slight monthly changes in the infection were noticed. Changes in infection were attributed to fish length, sex, food, water temperature and antagonism of N. iraqensis with the third larval stage of nematode Contracaecum in the studied fish.